Analisis Perlakuan Akuntansi atas Pendapatan Premi dan beban klaim Sesuai PSAK No. 28 pada PT. Asuransi Astra buana - Nataldy, Christian; Pardede, Robert Pius (Jurnal Ilmiah Akuntansi Kesatuan, 2019)
The development of the insurance industry is currently undergoing quite good progress. Based on data from OJK, the insurance industry has experienced an average growth of 16% for the past 4 years. This can be seen from the progress in investment growth which reached 14.40% and premium growth of 21.00%. This growth occurs because of the role of the insurance industry in serving the community to overcome risks. The insurance company will take the risk of the possibility that might occur to the community, such as loss or damage to the vehicle, fire, or the loss of natural disasters. The main source of insurance company income is from the sale of an insurance policy, which is in the form of insurance premiums given by the insured. And the insurance company's main burden is claim expense. Expenses incurred by insurance companies for reimbursement for a number of losses incurred by the insured. The purpose of this study was to find out how the accounting treatment of premium income and claim expenses in accordance with PSAK No. 28 at PT. Asuransi Astra Buana/PT. AAB. The results of the analysis of the accounting treatment of premium income and claim expenses at PT. AAB is in accordance with PSAK No. 28. Premium income is recognized and recorded at the time of issuance of the policy and presented in the financial statements in the form of gross premiums, premiums paid to reinsurers and a decrease (increase) in premiums which are not yet income. While claim expenses are recognized and recorded when the company arises to fulfill claims. Claim expenses are presented in the financial statements in the form of gross claims, reinsurance claims received from reinsurers and an increase (decrease) in estimated own retention claims. Compliance with PSAK No. 28 which has been carried out by PT. AAB needs to be maintained, in line with the developments in the PSAK, to avoid any errors in the recognition of premium income and claim expenses.